Formation of Values Through Chhau Nach In Purulia District - Laxmiram Gope; Sandip Mahato; Arif Ansari; Shaktipada Mahato (Journal of Advanced Research in Journalism & Mass Communication, 2021)
“Keep your habits positive because your habits become your values. Keep your values positive because your values become your destiny” - Mahatma Gandhi Value formation is the confluence of people’s personal experiences and particular culture they are entwined in. Values are imposed from their family in childhood and reinforced through culture and life experiences. Culture plays an important role in forming people’s values. Culture gives them a community and shared reality so that they can cooperate in activities and customs that give meaning. The main objective of this study is to seek the importance of Chhau Nach for the formation of values. Chhau Nach is enjoyed by every Purulian. People’s moral, personal, social, democratic values are shaped by Chhau Nach. This study is descriptive –cum survey type. The researchers themselves interviewed the Chhau artists. They extracted their views by asking various questions. The researchers have also taken the help of secondary data. Internet was the only source for the collection of secondary data. The researchers took the help of essays and articles from the internet in writing this paper. Through this study they learn that ChhauNach plays a significant role in forming the values of the Purulians. ChhauNach shapes their personal values by showing various episodes from Ramayana, Mahabharata and Puranas. A ChhauNach artist takes ideas from the culture of Purulia and eventually shapes the cultural values of the Purulians. The artists in a different style portrays the characters like Ganesha, Durga, Shiva etc. Thus, through the portrayal of such characters the Chhau artists forms the moral values of the Purulians.ChhauNach shapes people’s social values and teaches them to live in peace and harmony. How to cite this article: Mahato S, Ansari A, Gope L et al. Formation of Values through Chhau Nach in Purulia District. J Adv Res Jrnl Mass Comm 2020; 7(3): 11-15.